Guidelines for use of vapor cloud dispersion models. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1996)
The second edition of this essential reference updates and combines two earlier titles to capture the many technological advances for predicting the "footprint" of a vapor cloud release. Cited by EPA in its 1996 document, "Off-Site Consequence Analysis Guidance," the aim of the book is to encourage and facilitate the development and use of dispersion modeling as an everyday tool, providing practical understanding of basic physical and chemical principles, guidance in selecting release scenarios and the best available models, and information and examples on how to run some m.